Antibiotic resistance in Escherichia coli in husbandry animals: the African perspective - (:unkn) unknown (My University, 2017)
In the last few years, different surveillances have been published in Africa, especially in northern countries, regarding antimicrobial resistance among husbandry animals. Information is still scarce, but the available data show a worrying picture. Although the highest resistance rates have been described against tetracycline, penicillins and sulphonamides, prevalence of plasmid-mediated quinolone resistance genes and extended spectrum -lactamase (ESBL) are being increasingly reported. Among ESBLs, the CTX-M-1 group was dominant in most African surveys. Within this group, CTX-M-15 was the main variant both in animals and humans, except in Tunisia where CTX-M-1 was more frequently detected among Escherichia coli from poultry. Certain bla(CTX-M-15)-harbouring clones (ST131/B2 or ST405/D) are mainly identified in humans, but they have also been reported in livestock species from Tanzania, Nigeria or Tunisia. Moreover, several reports suggest an inter-host circulation of specific plasmids (e.g. bla(CTX-M-1)-carrying IncI1/ST3 in Tunisia, IncY- and Inc-untypeable replicons co-harbouring qnrS1 and bla(CTX-M-15) in Tanzania and the worldwide distributed bla(CTX-M-15)-carrying IncF-type plasmids). International trade of poultry meat seems to have contributed to the spread of other ESBL variants, such as CTX-M-14, and clones. Furthermore, first descriptions of OXA-48- and OXA-181-producing E.coli have been recently documented in cattle from Egypt, and the emergent plasmid-mediated colistin resistance mcr-1 gene has been also identified in chickens from Algeria, Tunisia and South Africa. These data reflect the urgent need of a larger regulation in the use of veterinary drugs and the implementation of surveillance programmes in order to decelerate the advance of antimicrobial resistance in this continent.
Keywords: African Research